PARENTING STYLE DALAM PERSPEKTIF AL-QUR’AN (Analisis Ayat-Ayat Al-Qur’an Yang Berkaitan Dengan Istilah Anak) - Aas Siti Solichah; Muhammad Hariyadi; Nurbaeti (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2021)
This paper aims to determine parenting styles developed in theperspective of the Qur’an. The research method developed is a qualitative research method with a literature study approach and an approach to the interpretation of the verses of the Al-Qur’an by using the maudu’i interpretation. In the Al-Qur’an parenting is divided into twa, namely parenting which is carried out by following the rules of the Al-Qur’an and Sunnah and Parenting that is not in accordance with the rules of the Al-Qur’an. Both of the these parenting styles will have an effect on children’s lives. Children who are raised with parenting in accordance with the provisions of the al-Qur’an and Sunnah will create children as soothing hearts and become jewelry. Meanwhile, shildren who are educated in parenting styles who are not touched by the Al-Qur’an will make the child an enemy for their parents.